Upaya Mengatasi Kemiskinan melalui Monitoring Program Hibah Kolega (Kolam Lele Keluarga) Kabupaten Malang - Sinollah; Denok Sekar Sari; Kharisma Maharani (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2025)
The KOLEGA (Family Catfish Pond) Grant Program is a strategic program designed to alleviate poverty through the empowerment of catfish farming groups. The program aims to help poor families by forming catfish farming groups, where the harvest can be utilized through sales as a source of additional income. This service research aims to understand the extent to which the KOLEGA grant program, implemented by the Fisheries Service in the Department of Small Fish Farmer Empowerment, contributes to reducing poverty levels. The methods used in this service include identification and coordination with various stakeholders, including the Fisheries Service and other related parties. Monitoring results in 2024 showed that the harvest of catfish cultivation has provided tangible benefits to grantee group members, both as an additional source of income and as animal protein consumption for the family. The program evaluation also revealed a number of obstacles in its implementation, which need to be overcome to improve the effectiveness and sustainability of the program in the future. These findings are expected to serve as the basis for further strategy development in efforts to alleviate poverty through the fisheries sector in Malang District